Brend equity as a relationship definition tool: defining the relationship between bottled water brands and Capetonian millennials during a time of drought - Reynecke, Hendrik (The IIE, 2018)
Marketing literature states that the concept of brand equity originates from an attempt to define the relationship between customers and brands. This was yet to be tested. The aim of this research study was to explore Keller’s customer-based brand equity (CBBE) model as a tool to define the brand relationship between bottled water brands and Capetonian millennials during a time of drought. Keller’s CBBE model claims that brand equity stems from the consciousness of customers, necessitating a qualitative research approach. To collect data, an online survey was distributed on social media and instant messaging platforms. This method allowed for more data from a bigger sample of Capetonian millennials. The brand equity pyramid associated with Keller’s CBBE model inspired the questions in the survey. Data was also analysed and interpreted according to the dimensions of the CBBE pyramid. The study found that there is merit to using Keller’s CBBE model as a tool to define brand relationships. The results could identify the weak relationship between bottled water brands and Capetonian millennials, providing significant insight into the causes and reasons for the relationship. Those insights could be used to address relationship weaknesses in the effort to achieve brand resonance.
Keywords: Brand equity; Brands; Customer-based brand equity; Bottled water brands; Millennials; Brand relationship; Brand resonance; Drought